PENDAMPINGAN LIVE STREAMING TIKTOK UNTUK MENINGKATKAN ENGAGEMENT DAN BRAND AWARENESS DI PT GAIDO BAROKAH KUDUS - Angelika IsmatuL Chawa; Lorena Dara Putri Karsono (IJTIMA’: JURNAL PENGABDIAN MASYARAKAT, 2026)
This community service program aims to assist the administrative staff of PT Gaido Azza Darussalam Indonesia Barokah Kudus in implementing TikTok live streaming as a primary focus of their Sharia marketing and education strategy, with the primary goal of increasing the company's digital engagement and brand awareness. We implemented a hands-on training method through simulations and gradual mentoring. This method prioritizes real-world practice, in line with Islamic communication principles, namely honest, responsive, and open information delivery. The results were very positive, as the program successfully improved the administrative staff's technical skills and confidence in conducting their own live broadcasts. Measurably, live streaming has been proven to create strong two-way interactions, with one broadcast session recording up to 63 views and 35 significant comments. This demonstrates that live streaming is highly effective in bridging face-to-face services with the desires of a digital audience seeking fast and personalized interactions. To ensure the sustainability of this strategy, companies are advised to immediately establish an internal team of experts and develop Standard Operating Procedures (SOPs).